2000
DOI: 10.1007/s002210000471
|View full text |Cite
|
Sign up to set email alerts
|

Proprioceptive population coding of two-dimensional limb movements in humans: I. Muscle spindle feedback during spatially oriented movements

Abstract: The proprioceptive coding of multidirectional ankle joint movements was investigated, focusing in particular on the question as to how accurately the direction of a movement is encoded when all the proprioceptive information from all the muscles involved in the actual movement is taken into account. During ankle movements imposed on human subjects, the activity of 30 muscle spindle afferents originating in the extensor digitorum longus, tibialis anterior, extensor hallucis longus and peroneus lateralis muscles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 28 publications
3
69
0
Order By: Relevance
“…The right foot was laid on a stationary plate, and the left foot was attached to a rotating pedal connected to a computer-controlled machine. This movable machine allowed two-dimensional movements to be imposed (see Bergenheim et al 2000). On the front plane of the machine (y, vertical axe), a downward (90°) or upward (270°) movement created a plantar flexion or dorsiflexion of the ankle joint, respectively.…”
Section: Experimental Setup and Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…The right foot was laid on a stationary plate, and the left foot was attached to a rotating pedal connected to a computer-controlled machine. This movable machine allowed two-dimensional movements to be imposed (see Bergenheim et al 2000). On the front plane of the machine (y, vertical axe), a downward (90°) or upward (270°) movement created a plantar flexion or dorsiflexion of the ankle joint, respectively.…”
Section: Experimental Setup and Protocolmentioning
confidence: 99%
“…A sideward movement (x, horizontal axe) to the left (180°) or to the right (0°) resulted in an eversion or inversion of the foot, respectively. Here ramp-and-hold movements were imposed in the preferred sensory direction of the receptor-bearing muscle, i.e., 59, 73, 96, and 311°for afferents belonging to EDL, EHL, TA, and PL muscles, respectively (see Bergenheim et al 2000). The components of each movement along the horizontal (x) and vertical (y) axes were sampled at 100 Hz.…”
Section: Experimental Setup and Protocolmentioning
confidence: 99%
“…At the ankle joint it has been shown that muscle spindle information from several muscles contributes to ankle proprioception [5]. It has been suggested that a large distribution of pain can interfere with proprioception by disturbing a large number of muscle spindles.…”
Section: Effkct Of Baseline Joint Position Sense On Change In Joint Pmentioning
confidence: 99%
“…First, microneurography serves to record feedback messages triggered in populations of afferents from all the muscles surrounding a given joint in response to two-dimensional movements performed under active and passive conditions Cordo et al 2002;Jones et al 2001;Roll et al 2000Roll et al , 2004. In addition, the "population vector model," first used at the cortical level (Georgopoulos 1982), was adapted to ensembles of somesthetic sensory neurons and to the particular anatomical and physiological organization of the cutaneous and muscular systems (Aimonetti et al 2007;Bergenheim et al 2000;Jones et al 2001;Roll et al 2000). Indeed, the muscle spindles merge into a very homogeneous population inside the muscle that bears them.…”
Section: Introductionmentioning
confidence: 99%
“…The direction of this population vector is the Preferred Sensory Direction of a given muscle (i.e., the average of the preferred sensory directions of all the muscle spindles in that muscle), whereas its module is proportional to the mean firing rate. By taking the sensory activity originating from all the muscles of a given joint, it was demonstrated that the neurosensory sum vectors are highly correlated with the movement vectors at any point of a given trajectory (Albert et al 2005(Albert et al , 2006Bergenheim et al 2000;Jones et al 2001). Consequently, each sum vector gives the instantaneous direction and velocity of the ongoing movement (i.e., its tangential velocity).…”
Section: Introductionmentioning
confidence: 99%